Intracellular colonization of Rhododendron and Vaccinium roots by Cenococcum geophilum, Geomyces pannorum and Meliniomyces variabilis - Vohník, M; Fendrych, M; Albrechtová, J; Vosátka, M (Folia microbiologica, 2007)
Four in vitro experiments were set up to verify the colonization potential of ectomycorrhizal (EcM) Cenococcum geophilum FR. (strain CGE-4), saprotrophic Geomyces pannorum (LINK) SIGLER & CARMICHAEL (GPA-1) and a frequent root-associated, potentially ericoid mycorrhiza (ErM)-forming Meliniomyces variabilis Hambleton & Sigler (MVA-1) in roots of Rhododendron and Vaccinium. A typical ErM fungus, Rhizoscyphus ericae (Read) Zhuang & Korf (RER-1), was included for comparison. All fungal strains intracellularly colonized rooted Vaccinium microcuttings: GPA-1 occasionally produced hyphal loops similar to ErM, MVA-1 and RER-1 exhibited a typical ErM colonization pattern. CGE-4 hyphae grew vigorously on and around newly formed roots and rarely penetrated turgescent rhizodermal cells forming intracellular loose loops. Rooting of Rhododendron sp. microcuttings was not promoted by any fungal strain except CGE-4, which also promoted the most vigorous growth of Rhododendron ponticum L. seedlings. The widespread EcM fungus C. geophilum has a potential to colonize non-EcM roots and support their development which may influence overall growth of ericaceous plants. As shown for G. pannorum, structures resembling ErM may be formed by fungi that are to date not regarded as ericoid mycorrhizal.
Keywords: Rhododendron; Ascomycota; Chrysosporium; mykorhiza; kořeny rostlin; Plant Roots; Mycorrhizae; Microscopy, Interference; Vaccinium; interferenční mikroskopie